Price formation and intertemporal arbitrage within a low-liquidity framework: Empirical evidence from European natural gas markets - Sebastian Nick (Institute of Energy Economics at the University of Cologne (EWI), 2013)
In this study, the informational efficiency of the European natural gas market is analyzed by empirically investigating price formation and arbitrage efficiency between spot and futures markets. Econometric approaches are specified that explicitly account for nonlinearities and the low liquidityframework of the considered gas hubs. The empirical results reveal that price discovery takes place on the futures market, while the spot price subsequently follows the futures market price. Furthermore, there is empirical evidence of significant market frictions hampering intertemporal arbitrage. UK's NBP seems to be the hub at which arbitrage opportunities are exhausted most efficiently, although there is convergence in the degree of intertemporal arbitrage efficiency over time at the hubs investigated.
Keywords: Q40; Q41; G14; C58; 330; natural gas market; informational efficiency; liquidity; nonlinear causality; threshold error correction; Kalman filter